2014
DOI: 10.4187/respcare.03315
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Difficult-to-Wean Subjects After Cardiac Surgery

Abstract: BACKGROUND:The need for prolonged mechanical ventilation (PMV) after cardiac surgery is still a common problem. We hypothesized that subjects who required PMV after a single surgery (either coronary artery bypass grafting or valve surgery) would have better outcomes than those who had experienced both revascularization and valve surgery. METHODS: We retrospectively analyzed the characteristics and outcomes for patients consecutively admitted to our weaning unit (WU) after cardiac surgery between December 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] One recent large-scale study reported a 7% rate of post-operative ventilation for more than 48 h after cardiac surgery with an inhospital death rate of 22.3%. The condition of PMV after cardiac surgery has long been the focus of clinical research, as it was early shown to be associated with an adverse clinical outcome and increased mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5][6][7][8][9] One recent large-scale study reported a 7% rate of post-operative ventilation for more than 48 h after cardiac surgery with an inhospital death rate of 22.3%. The condition of PMV after cardiac surgery has long been the focus of clinical research, as it was early shown to be associated with an adverse clinical outcome and increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies aimed to decipher the aetiology and clinical implications of PMV in this setting. [1][2][3][4][5][6][7][8][9] One recent large-scale study reported a 7% rate of post-operative ventilation for more than 48 h after cardiac surgery with an inhospital death rate of 22.3%. 9 Circulatory assist devices were though excluded from these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inappropriate decision making regarding weaning and extubation readiness also is not without risk. Patients may experience respiratory and cardiac failure associated with increased work of breathing during the reduction of ventilatory support for weaning (Jeganathan et al, 2015;Vagheggini et al, 2015). Reintubation due to postextubation respiratory failure has been shown to increase mortality from 2.5 to 10 times compared to patients that do not require reintubation (Rothaar and Epstein, 2003).…”
Section: Introductionmentioning
confidence: 99%